Selection of rehabilitation construction solutions - Silva, Sandra Monteiro (2012)
Building rehabilitation is essential to achieve the targets defined by the EPBD-recast regarding energy efficiency. Besides the energy efficiency the Indoor Environmental Quality (IEQ) and environmental impact must also be considered when planning a rehabilitation project. Thus to propose an effective building rehabilitation it is necessary to select the adequate construction solutions taking into account their impact on the energy performance, thermal and acoustic comfort and environmental impact of the building. In this work, ELECTRE III method is applied to assist the design team on the selection of construction solutions. A simple case study is presented to show this approach in what concerns the selection of construction solutions (thickness and placement of insulation materials and construction solution options) of a rehabilitation project.